A new species of the genus Microgecko Nikolsky, 1907 (Sauria: Gekkonidae) from southern Iran - Gholamifard, Ali; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar; Khosravani, Azar; Yousefkhani, Seyyed Saeed Hosseinian; Oraei, Hamzeh (Zootaxa, 2016)
The dwarf geckos of the recently revived genus Microgecko Nikolsky, 1907 comprise four species, ranging from western Iran to northwestern India. Iran hosts three species of the four recognized species of the genus Microgecko. Here, we describe a new species of this genus based on two and single specimens from southeastern and southern Iran, respectively. Combinations of scalation characters and distinct morphology, coloration and habitat peculiarities in calcareous mountains distinguish Microgecko chabaharensis sp. nov. from its congeners. Detailed information and an updated identification key for the genus Microgecko are also presented.